Improving Police Performance through Human Resource Quality, Motivation, Discipline, and Organizational Culture - Andy Eka Apriyanto; Hafidulloh Hafidulloh; Endri Haryati (UMSurabaya Publishing, 2026)
The West Surabaya Police Department represents a police organization in an urban area with a high level of task complexity. It exhibits significant variation in personnel performance, with some members still receiving ratings in the